The Local-Ladder Effect - Anderson, Cameron; Kraus, Michael W.; Galinsky, Adam D.; Keltner, Dacher (Psychological Science, 2012)
Dozens of studies in different nations have revealed that socioeconomic status only weakly predicts an individual's subjective well-being (SWB). These results imply that although the pursuit of social status is a fundamental human motivation, achieving high status has little impact on one's SWB. However, we propose that sociometric status-the respect and admiration one has in face-to-face groups (e.g., among friends or coworkers)-has a stronger effect on SWB than does socioeconomic status. Using correlational, experimental, and longitudinal methodologies, four studies found consistent evidence for a local-ladder effect: Sociometric status significantly predicted satisfaction with life and the experience of positive and negative emotions. Longitudinally, as sociometric status rose or fell, SWB rose or fell accordingly. Furthermore, these effects were driven by feelings of power and social acceptance. Overall, individuals' sociometric status matters more to their SWB than does their socioeconomic status.